2020
DOI: 10.1177/0258042x20959998
|View full text |Cite
|
Sign up to set email alerts
|

Fair Treatment for All: Testing the Predictors of Workplace Inclusion in a Canadian Police Organization

Abstract: The growing diversification of the workforce demands that organizational leaders create workplaces in which individuals have a sense of belonging and are valued for their unique contributions. However, beyond the contributions of certain types of leadership, there is insufficient understanding of the factors that impact experiences of workplace inclusion. Using survey data collected from a Canadian police organization ( N = 488) in the spring of 2018, this study examined whether organizational justice (i.e., f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 77 publications
3
10
0
Order By: Relevance
“…inclusive climate and culture for inclusion, workplace inclusion and inclusive leadership. Workplace inclusion is found to be associated with practices characterized by an organizational culture of inclusion theorized in Nishii (2013), such as fair treatment for all (Workman-Stark, 2021), equitable employment practices (Le et al , 2020), inclusion in decision-making (Bodla et al , 2018), inclusive behavior (Nelissen et al , 2017) and inclusive leadership (Brimhall et al , 2016). Prior studies have documented complexities in creating these practices.…”
Section: Inclusion Measurements and Initial Empirical Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…inclusive climate and culture for inclusion, workplace inclusion and inclusive leadership. Workplace inclusion is found to be associated with practices characterized by an organizational culture of inclusion theorized in Nishii (2013), such as fair treatment for all (Workman-Stark, 2021), equitable employment practices (Le et al , 2020), inclusion in decision-making (Bodla et al , 2018), inclusive behavior (Nelissen et al , 2017) and inclusive leadership (Brimhall et al , 2016). Prior studies have documented complexities in creating these practices.…”
Section: Inclusion Measurements and Initial Empirical Findingsmentioning
confidence: 99%
“…The relationship between workplace inclusion and psychological safety could be reciprocal. The more people indicate that their workplace is psychologically safe, the more they feel included (Workman-Stark, 2021).…”
Section: Inclusion Measurements and Initial Empirical Findingsmentioning
confidence: 99%
“…This position is supported by a meta-analysis conducted by Wolfe and Lawson (2020) , who conclude that organisational justice is a key predictor of critical outcomes among criminal justice system employees. Workman-Stark (2021) argues that creating a just organisational climate is essential for maintaining individual employee satisfaction and ensuring organisational effectiveness, particularly during periods of uncertainty. The extraordinary policing situation arising as a consequence of the pandemic presented a uniquely unpredictable and challenging environment for police practitioners; one within which police organisations may have had trouble in observing or maintaining principles that create the sense of a ‘just climate’ organisationally.…”
Section: Introductionmentioning
confidence: 99%
“…Considering inclusion's importance, it is critical to have a clear understanding of the factors and causes that enable its occurrence in organizations. However, many researchers have indicated that although the outcomes and contributions of inclusion have been identified in many studies, its determinants and the factors contributing to it remain unclear and not defined to the fullest (Brimhall et al, 2016;Qu et al, 2021;Workman-Stark, 2021). In their model, Shore et al (2011) have identified 3 predictors of inclusion: (1) a climate that includes diversity and fair systems,…”
Section: Inclusionmentioning
confidence: 99%
“…To add more, leadership was found to be one of inclusion's antecedents, especially authentic leadership (Cotrill et al, 2014) and ethical, responsible leadership that consistently responds to society (Mousa & Puhakka, 2019). In addition, some more antecedents of inclusion were shown to be the quality of leader-follower interactions (Brimhall et al, 2016), leader engagement (Brimhall, 2019), a diversity climate and leader inclusiveness (Chung et al, 2020) and organizational justice (Martin & Zyphur, 2021;Workman-Stark, 2021).…”
Section: Inclusionmentioning
confidence: 99%